Bismuthyl chloride/poly(m-toluidine) nanocomposite seeded on poly-1H pyrrole: Photocathode for green hydrogen generation - Alnuwaiser Maha Abdallah; Rabia Mohamed; Elsayed Asmaa M. (Open Physics)
A novel photocathode has been developed for H2 gas generation from sewage water, utilizing a bismuthyl chloride–poly m-toluidine (BiOCl–PMT) nanocomposite supported on poly-1H pyrrole (P1HP). X-Ray photoelectron spectroscopy analysis confirms the formation of bismuth oxide intercalated within the polymer network through a chemical reaction, resulting in the creation of bismuth oxide chloride (BiOCl). This photocathode exhibits strong absorption in the UV region, extending into the visible spectrum, with a bandgap of 2.75 eV, enabling effective interaction with photons and efficient energy transfer to the photocatalyst nanomaterials. The material’s crystalline size is limited to 39 nm, and it features a highly porous polymer structure with a pore size of 20 nm, aggregating into larger structures approximately 300 nm thick. When employed as the working electrode in a three-electrode cell, the BiOCl/PMT/P1HP photocathode shows a measured photocurrent density (J ph) of −0.046 mA/cm² under illumination, which drops to −0.032 mA/cm² when the light is turned off. The resulting photocurrent of 0.012 mA/cm² reflects the photocathode’s efficient photoelectrochemical behavior. The performance of the photocathode during sewage water splitting can be adjusted by varying the photon energies between 3.6 and 1.7 eV, using filters to control photon wavelengths. This variation is evident in the linear sweep voltammetry curves, with J ph values ranging from −0.045 mA/cm² at 3.4 eV to about −0.042 mA/cm² at 1.7 eV under an applied bias voltage of −0.7 V. The photocathode’s high efficiency is further demonstrated by its ability to produce 15 µmol/h of H2 gas for a 10 cm² area. This promising performance, combined with cost-effectiveness, makes the BiOCl/PMT/P1HP photocathode an attractive option for green chemistry and industrial applications.